High Electrochemiluminescence from Ru(bpy)32+ Embedded Metal–Organic Frameworks to Visualize Single Molecule Movement at the Cellular Membrane. Issue 35 (3rd November 2022) - Li, Binxiao; Huang, Xuedong; Lu, Yanwei; Fan, Zihui; Li, Bin; Jiang, Dechen; Sojic, Neso; Liu, Baohong
Abstract: Direct imaging of single‐molecule and its movement is of fundamental importance in biology, but challenging. Herein, aided by the nanoconfinement effect and resultant high reaction activity within metal–organic frameworks (MOFs), the designed Ru(bpy)3 2+ embedded MOF complex (RuMOFs) exhibits bright electrochemiluminescence (ECL) emission permitting high‐quality imaging of ECL events at single molecule level. By labeling individual proteins of living cells with single RuMOFs, the distribution of membrane tyrosine‐protein‐kinase‐like7 (PTK7) proteins at low‐expressing cells is imaged via ECL. More importantly, the efficient capture of ECL photons generated inside the MOFs results in a stable ECL emission up to 1 h, allowing the in operando visualization of protein movements at the cellular membrane. As compared with the fluorescence observation, near‐zero ECL background surrounding the target protein with the ECL emitter gives a better contrast for the dynamic imaging of discrete protein movement. This achievement of single molecule ECL dynamic imaging using RuMOFs will provide a more effective nanoemitter to observe the distribution and motion of individual proteins at living cells. Abstract : Ru(bpy)3 2+ in single nanoporous metal–organic frameworks complex (RuMOFs) is designed as novel nanoemitter with high electrochemiluminescence (ECL), which permits the collection of discrete ECL events at single molecules level. Near‐zero ECL background surrounds the target labeled with the confinement‐enhanced emitter, achieving unprecedentedly the visualized dynamic characteristics monitoring of individual proteins at different living cells surface.